The Importance of Leardership in Business - Mirna; Hasna B; Alwan Suban (Business Finence Analyst Co.,, 2025)
This article aims to explain the importance of leadership in business because it can help achieve long-term success. This research uses a type of library research using a qualitative approach. Data sources obtained through literature reviews relevant to the importance of leadership in business. This research discusses several topics including: 1) the concept of leadership; 2) leadership style in management; 3) entrepreneurial leadership, and 4) leaders' efforts to face business challenges. Data collection techniques involve systematic literature searches, analysis and topic searches regarding the importance of leadership in business. Based on the studies conducted, it can be seen that the importance of leadership in business is because it can improve business targets for quality in achieving predetermined goals. Keywords: Leadership, Leader, business